Detection of blaOXA-48 and clonal relationship in carbapenem resistant K. pneumoniae isolates at a tertiary care center in Western Turkey. Issue 5 (September 2018) - Ece, Gulfem; Tunc, Emine; Otlu, Baris; Aslan, Deniz; Ece, Cem
Abstract: Background: Klebsiella pneumoniae is an important nosocomial pathogen that can lead to high morbidity and mortality. ESBL and carbapenamase producing strains may cause epidemic situations. The aim of our study was to investigate the molecular epidemiology and clonal relationship between carbapenem resistant K. pneumoniae strains isolated from our hospital during a three month period. Methods: Fourteen carbapenem resistant K. pneumoniae strains isolated during April 1st–June 30th 2013 were included. The identification and the antibiotic susceptibility of the strains were studied by Vitek 2 Compact (Biomerieux, France) system. The carbapenemase production of the isolates were investigated by Modified Hodge assay. The blaOXA of the strains was investigated by in house PCR. The clonal relationship between the isolates were studied by pulsed-field gel electrophoresis (PFGE) and automatized repetitive extragenic palindromic PCR (Rep-PCR, DiversiLab sistemi, Biomerieux, France) methods. Results: All the K. pneumoniae isolates were carbapenem resistant; they were all susceptible to gentamycin and colistin. All of them had blaOXA-48 . The genotyping analysis revealed that eight isolates were in the same cluster both by Rep-PCR (similarity border ≥95%) and PFGE (Tennover criteriae) analysis. The other isolates did not belong to any other clusters. The strains that are in the same cluster are isolated from the Anesthesiology Intensive Care Unit during a three month period. The cluster ration by both methods was 57%. Conclusions: All K. pneumoniae strains possessed bla OXA-48. The clonal spreading was particularly detected in Anesthesiology Intensive Care Unit. Molecular epidemiological monitorization of nosocomial pathogens may prevent the spread of these multidrug resistant pathogens.